Štirje principi vzgoje na primeru majevske kulture iz Chiapasa in Jukatana - Terčelj, Marija Mojca (Etnolog. Nova vrsta (Ljubljana), 2007)
The present article, which focuses on a non-European area, is an attempt to present the inclusion of children in the wider social environment and is basedon a comparison between family education and education in government education processes, that is between the Mountain Maya in Chiapas and the Maya of Yucatan; it further addresses some issues deriving from the confrontation of these two uncoordinated approaches to education. The principal differences between the education provided by a family environment and the education principles asserted by modern education science lie in the close links between family members and education towards autonomy, responsibility and respect in the Indian communities, and towards dependence, partialisation and alienation in the case of modern approaches to education.
Keywords: vzgoja; družina; education; family; vrednote; indigenizem; values; izobraževalni projekti; indigenism; education projects; Chiapas; Jukatan; Yucatan